Two new species of Empoascanara Distant (Hemiptera: Cicadellidae: Typhlocybinae) from Yunnan Province, China - Song, Yue-Hua; Li, Zi-Zhong (Zootaxa, 2013)
Two new species, Empoascanara conchata, E. longiaedeaga spp. nov. from Yunnan are described and illustrated, and a key to the species recorded from China is provided.